ANALISIS KINERJA KEUANGAN PADA KOPERASI SERBA USAHA WANITA NEKMESE SEJAHTERA KABUPATEN TTU - Ningsi, Putri Ratna; Duli, Dominikus Kopong (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2021)
Cooperatives are business entities formed by members of people on the basis of common interests. Members raise capital in the form of basic, mandatory, voluntary savings, which are managed efficiently. The capital raised is managed honestly, efficiently and responsibly. The use of capital must be efficient by considering the level of liquidity and profitability. To assess financial performance, an analysis is carried out to describe the performance of healthy management or vice versa. Liquidity describes the ability to pay off debts that are repaid immediately. Profitability describes the ability to use capital to make a profit. The higher the profit, the better the health of the cooperative, and vice versa. The results of the analysis in the last three years (2018, 2019, 2020) show that Liquidity is in poor criteria both from the Current Ratio aspect and the Quick Ratio aspect . Meanwhile, from the profitability aspect, both the Return Of Investment aspect and the Return Of Equity aspect are in good condition